Assessment of Serum C-Reactive protein (CRP) to Albumin ratio and Serum Uric acid to Albumin ratio as markers of inflammation in patients with Type 2 Diabetes Mellitus - Kiran N, Asha; Sirish, A.; Sravani, K.; Ramakrishna, N.; Kumar, E. Kiran (Journal of Neonatal Surgery, 2025)
Background: Diabetes Mellitus (DM) is a chronic condition that develops when the pancreas does not produce sufficient amount of insulin or the body cannot effectively utilize it. Uncontrolled type 2 diabetes mellitus (T2DM) is associated with the risk of developing micro- and macro-vascular complications. Inflammation is associated with the pathogenesis of T2DM. Aim: This study aimed to assess the serum C-Reactive protein (CRP) to Albumin ratio (CAR) and serum Uric acid to Albumin ratio (UAR) as markers of inflammation in patients with Type 2 Diabetes Mellitus. Materials and Methods: This retrospective study was conducted in the Department of Biochemistry in association with the Department of Pathology, Gayathri Vidhya Parishad Institute of Health Care & Medical Technology (GVPIHCMT), Visakhapatnam, Andhra Pradesh, India. After obtaining the Institutional Ethics Committee (GVPIHCMT/IEC/20250106/01), a total of 300 subjects’ data was collected. Among 300 subjects, 150 were type 2 diabetes mellitus patients and 150 were non-diabetic subjects. Necessary details were collected from medical records, including demographic details, biochemical parameters such as fasting and post-prandial glucose, urea, creatinine, uric acid, lipid profile parameters, HbA1c, and CRP were retrospectively reviewed from the electronic file system and file records of the participants. CAR value is determined by dividing the CRP level with the albumin level, and UAR value is determined by dividing the uric acid level with the albumin level. Results: In this study, a significant increase in mean age 51.5±10.3 years, BMI 27.5±2.2 kg/m2, systolic blood pressure 120.5±6.8 mmHg, and diastolic blood pressure 78.5±4.4 mmHg was observed in T2DM patients compared with non-diabetic subjects. In biochemical parameters, significant increase in fasting blood sugar 160.8±59.8 mg/dl, post-prandial blood sugar 205.8±55.7 mg/dl, HbA1c 7.2±2.7 g%, urea 35.7±9.9 mg/dl, creatinine 1.1±0.1 mg/dl, uric acid 7.1±1.3 mg/dl, total cholesterol 185.2±44.1mg/dl, triglycerides 165.1±35.7 mg/dl, LDLC 122.4±32.5 mg/dl, VLDLC 33.0±7.1 mg/dl, total bilirubin 0.7±0.1mg/dl, AST 40.2±8.5 IU/L, ALT 41.9±9.6, ALP 99.6±22.5 IU/L and significant decrease in HDLC 29.8±4.5 mg/dl, total proteins 5.1±1.2 g% and albumin 3.0±0.9 g% was observed in T2DM subjects than non-diabetic subjects. In inflammatory markers, CRP 10.1±1.5 mg/dl, CAR 3.3±1.6, and UAR 2.3±1.4 were significantly increased in T2DM subjects than non-diabetic subjects. FBS was significantly correlated with CRP (r=0.439), CAR (r=0.351), and UAR (r=0.215). HbA1c also showed a positive correlation with CRP (r=0.269), CAR (r=0.296), and UAR (r=0.448). Conclusion: This study results may conclude that significant increase in CRP, CAR, and UAR in patients with T2DM. Also, CRP, CAR, and UAR positively correlated with FBS and HbA1c.